Long-Duration Optical Pulse Shaping and Complex Coding on SOI - H. P. Bazargani; M. Burla; Z. Chen; F. Zhang; L. Chrostowski; J. Azana (IEEE Photonics Journal)
This paper evaluates novel design strategies to enhance the performance of a recently proposed waveguide-based pulse-shaping method, i.e., discrete space-to-time mapping (D-STM), demonstrating the capability of the method to shape pulse waveforms with duration periods in the tens of picoseconds regime. In particular, we experimentally synthesize 70-ps high-quality flat-top pulses and a 40-ps-long 200-GBd 16-quadrature amplitude modulation (16-QAM) data sequence using D-STM in concatenated co-directional couplers. Our proposed devices have been fabricated on a silicon-on-insulator (SOI) technology platform using ultraviolet and single-etch electron-beam lithography processes. The fabricated devices are all-passive, functioning without needing post-fabrication tuning, which further proves the robust performance of the proposed scheme.